2011
DOI: 10.21273/horttech.21.6.703
|View full text |Cite
|
Sign up to set email alerts
|

Root Piece Planting in Sweetpotato—A Synthesis of Previous Research and Directions for the Future

Abstract: Sweetpotato (Ipomoea batatas) is traditionally grown for fresh consumption, particularly in developed nations, but it is increasingly being used for alternative markets such as processed foods and industrial products. Sweetpotato is well suited for these end uses but its utilization is limited due to high production costs. These costs are primarily the result of high labor inputs. As a vegetatively propagated crop, sweetpotato is typically planted using unrooted plant cutting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
1
16
1
2
Order By: Relevance
“…We could not attribute the yield variation between sites and years was to environmental factors. This is in agreement with other studies of sweetpotato (Collins et al, 1987;George et al, 2011George et al, , 2014Gr€ uneberg et al, 2005;Kanua and Floyd, 1988;Manrique and Hermann, 2002;Ngeve, 1993). Clones planted as root pieces did not display greater instability than the same clones planted as slips, although factors influencing composition and yield did vary between clones and slips.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We could not attribute the yield variation between sites and years was to environmental factors. This is in agreement with other studies of sweetpotato (Collins et al, 1987;George et al, 2011George et al, , 2014Gr€ uneberg et al, 2005;Kanua and Floyd, 1988;Manrique and Hermann, 2002;Ngeve, 1993). Clones planted as root pieces did not display greater instability than the same clones planted as slips, although factors influencing composition and yield did vary between clones and slips.…”
Section: Discussionsupporting
confidence: 91%
“…Sweetpotato is relatively costly to produce, and to be economically viable as a carbohydrate crop steps need to be taken to reduce production costs. We compared conventional planting using slips to root pieces, which can be planted mechanically and potentially more cheaply (George et al, 2011). We found that planting method did not significantly influence root composition, however, clones planted from root pieces tended to have lower yields overall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ubi jalar (Ipomoea batatas L.) merupakan salah satu hasil panen yang sangat penting dengan produksi lebih dari 133 juta ton setiap tahunnya di seluruh dunia. Ubi jalar mudah dibudidayakan, dapat tumbuh pada berbagai macam jenis tanah, produktivitasnya tinggi, masa tanam relatif pendek (3-6 bulan), dan membutuhkan sedikit pupuk (George et al 2011). Sampai saat ini manisan ubi jalar belum terlalu dikenal oleh masyarakat.…”
Section: Pendahuluanunclassified